Revisiting complex azeotropic distillation design: How feed composition can change separation sequences - Yang, Zhenning; Gao, Tian; Yang, Ao; Sun, Shirui; Shi, Tao; Li, Zhongmei; Du, Wenli; Lin, Rongsheng; Kong, Zong Yang; Shen, Weifeng (Separation and purification technology, 2026)
The design of complex azeotropic distillation system are typically based on a fixed nominal feed composition, i.e., assuming the same process setup remains valid under expected disturbances. This sequential “control after design” strategy often overlooks a critical question: can variations in feed composition fundamentally alter the optimal separation sequence? In this work, we investigates the influence of feed composition on the optimal design and performance of a triple-column pressure-swing distillation with decanter (TCPSD-D) for multi-azeotropes system. Three configurations were developed under two different feed compositions to explore how product sequence, pressure requirements, and utility usage shift with changing feed conditions. While two configurations based on the same feed required pressure manipulation to alter the separation order, a third configuration using a different feed achieved the same sequence without elevated pressure. Optimization results revealed that although all columns in the third configuration operated with low-pressure steam, the use of chilled water in a vacuum condenser led to the highest overall cost. In contrast, the first configuration demonstrated the best cost–energy balance. These findings highlight the critical role of feed composition in early-stage process design, where it can fundamentally influence separation feasibility, utility strategy, and economic outcomes.